2001
DOI: 10.2307/3558443
|View full text |Cite
|
Sign up to set email alerts
|

Rice and Phragmites: effects of organic acids on growth, root permeability, and radial oxygen loss to the rhizosphere

Abstract: Young Phragmites plants were grown in two cocktails of monocarboxylic acids (C(1)-C(5)) at pH 6, where the concentration of each acid was innocuous and the total undissociated (potentially toxic) concentrations were 0.35 mmol/L and 0.42 mmol/L. Rice plants were subjected to 1.5 mmol/L acetic acid at pH 4.5 (undissociated concentration = 1.05 mmol/L). In Phragmites, each cocktail curtailed root growth especially and induced premature shoot senescence. In both species, after 3-5 d of treatment, radial oxygen los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
110
0
9

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(124 citation statements)
references
References 47 publications
5
110
0
9
Order By: Relevance
“…The cultivars Brisasul and FAEM 06 showed a linear decrease in RL, especially the cultivar Brisasul, which presented a RL of 9.02 cm in the control and 5.12 cm at the maximum level (12 mM). Root growth of rice seedlings was inhibited by acetic acid (Armstrong and Armstrong, 2001;Sousa and Bortolon, 2002). Another study with rice also showed that with higher levels of acetic acid reduces the RL, but low levels (<6.8 mM) allowed a slight increase (Neves et al, 2010).…”
Section: Resultsmentioning
confidence: 90%
“…The cultivars Brisasul and FAEM 06 showed a linear decrease in RL, especially the cultivar Brisasul, which presented a RL of 9.02 cm in the control and 5.12 cm at the maximum level (12 mM). Root growth of rice seedlings was inhibited by acetic acid (Armstrong and Armstrong, 2001;Sousa and Bortolon, 2002). Another study with rice also showed that with higher levels of acetic acid reduces the RL, but low levels (<6.8 mM) allowed a slight increase (Neves et al, 2010).…”
Section: Resultsmentioning
confidence: 90%
“…Thus, an efficient way of evaluating genotypes for tolerance to the presence of organic acids in culture media can be accomplished by using hydroponics under the controlled conditions. Since rice is the primary crop for lowland soils, efficient methodologies for evaluating the toxicity are described in the literature (Rao and Mikkelsen, 1977a,b;Camargo et al, 1993;Armstrong and Armstrong, 2001;Sousa and Bortolon, 2002). Since oat is still a minor crop in lowland areas, there have not been many studies focusing the evaluation of its response to excess organic acids, being a prior necessity the adjustment of a protocol for use in hydroponic systems aiming to identify the tolerant genotypes.…”
Section: Introductionmentioning
confidence: 99%
“…prejudicial na porcentagem de germinação para o processo de comercialização, ou seja, abaixo de 80%. Nas sementes de arroz, os ácidos orgânicos causam a degradação das membranas celulares e perda do conteúdo celular para o meio (KOPP et al, 2007b), mas também cultivares tolerantes devem possuir genes que conferem maior capacidade de formação de membranas celulares que tolerem esses ácidos (ARMSTRONG & ARMSTRONG, 2001). As sementes da cultivar 'IRGA 424' são de elevada capacidade germinativa, podendo ser consideradas insensíveis à toxicidade, devido à maior capacidade de manutenção celular em condição de estresse, causados pelos ácidos acético e butírico, nas concentrações inferiores a 8mM (Figura 1A).…”
Section: Resultsunclassified